EFEKTIVITAS PENGGUNAAN MODUL FISIKA TERINTEGRASI STEM (SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS) MATERI USAHA DAN ENERGI DI SMA - Ella Maria Ulfa; Subiki Subiki; Lailatul Nuraini (Universitas Jember, 2021)
Learning carried out during the pandemic is required to develop technology to support student learning effectively. Solutions for students and teachers to carry out learning effectively by using learning media that students can understand independently at home. Learning media that can support students in independent learning are modules. The module usage by educators related to 21st-century skills to balance the world of education in the modern era can collaborate with models, methods, and approaches in learning, one of which is the STEM (Science, Technology, Engineering, and Mathematics) approach. The purpose of this research is to describe the effectiveness of the STEM integrated physics module. The research method is by giving tests to students in the form of pretest and posttest. The subjects of this study were students of MAN 1 Jember class X MIPA 2 as a limited test and X MIPA 3 broad test. Product testing was conducted by researchers using the One Group Pretest-Posttest design. Then analyzed normalized Gain (N-gain) to determine the effectiveness of the module. The results of the analysis of the effectiveness of the module in the limited test obtained an average N-gain of 0.55 in the medium category, while in the broad test it was 0.71 in the high category. Based on the results of the effectiveness analysis that the STEM integrated physics module is in the effective category. Keyword: Module, STEM, efectivity